Numerical Investigation of Oil–Water Exchange Behaviors in Shale During Post-Fracturing Soaking Periods - Wang, Fei; Chen, Qiaoyun; Zhang, Jingchen; Ruan, Yingqi; Zhuang, Ye; Zhu, Jian; Zhang, Shicheng (Frontiers in Earth Science, 2021)
Fracturing fluid imbibition and retention are treated as a main mechanism for oil production from shale reservoirs. However, the oil–water exchange phenomenon during post-fracturing soaking periods has not been thoroughly studied. In this study, a water–oil flow model is built to investigate the water imbibition and oil drainage phenomenon in hydraulically fractured shale. With the developed numerical simulator, the main characteristics of post-fracturing soaking, that is, pressure diffusion, water imbibition, and especially, the oil–water exchange behavior are simulated. Three key time points, that is, oil–water exchange equilibrium, steady exchange efficiency, and oil breakthrough in fracture are found. The oil–water exchange efficiency and exchange volume are also calculated. Moreover, the proposed model is validated by field wellhead pressure dynamics, indicating a relevance of time between the oil–water exchange efficiency and the wellhead pressure falloff derivatives. Finally, the influences of shale permeability, wettability, fracture complexity, and oil viscosity on the oil–water exchange behavior are investigated. Results indicate that the matrix of oil-wet shale almost does not suck water and discharge oil, and only the oil in natural fractures exchanges with the water in hydraulic fractures. The water-wet shale with low permeability, high oil viscosity, and few natural fractures needs extra soaking time to achieve good oil–water exchange performance. The suitable soaking period for the water-wet base case in this study is from 17.25 to 169 days, among which 64 days is the optimal soaking time.